(untitled) (Quinto Sol, 2018)
Catholic protagonism is usually one of the explanatory elements concerning the emergence of “peronismo extracéntrico”. This article, which focuses on the Argentine Province of Santiago del Estero, proposes to look at the connections between Peronism and Catholicism from a broader temporal context, giving account of a long process of political-religious exchanges and disputes that were developing in the social space from the late 19th century. The diachronic dimension of the analysis gains a methodological sense by referring to a framework of reconfigurations, on the place of the religious in relation to politics and State. It analyzes ideas, groups and agents that carried out some critical junctures of symbolic disputes on a provincial scale, showing that the emergency situation of Peronism is connected with other “windows of opportunity” in which Catholicism was able to dispute senses and criteria of legitimation. In this context, belonging to spaces of socialization and Catholic militancy of political actors in times of emergence of Peronism does not seem an unprecedented phenomenon in the social space of Santiago and opens a set of questions about the complexities of the relationships between Catholicism and Peronism.